PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN JASA APOTEK BAYA HUSADA BOYOLALI - Aji, Ambyah Atas; Widiastuti, Erni (ITB AAS Indonesia Surakarta, 2024)
This study aimed to see if there are service quality affects customer satisfaction in using the services of Pharmacy Baya Husada Boyolali. Subjects in this study is that consumers Pharmacy Baya Husada Boyolali aged 18-60 years; purchase drugs at private expense; able to read, write, and communicate well; and willing to fill out a questionnaire. This study uses quantitative research methods, to determine the effect of service quality on consumer satisfaction using the services of the pharmacy Baya Husada Boyolali. The samples used in this study was 116 subjects. Measurements in this study was performed using a questionnaire based on the variables used. Data were analysed using classical assumption test and multiple regression analysis. Based on the analysis and discussion of the quality of service showed that the appearance of Pharmacy, Hospitality Officer, Drug Information Service at the pharmacy, Availability of Medicines in Pharmacies, Pharmacy Services and Speed affects customer satisfaction in using Pharmacy Baya Husada Boyolali. Keyword : service quality, quality of service, consumer satisfaction